Selected Income Tax Reliefs as Instruments Supporting Sustainable Development in Poland (Ius Novum, 2026)
Measures for sustainable development may involve both increasing taxes and introducing new taxes levied on taxpayers failing to pursue this goal, and preferential treatment for entities operating in a way that implements the sustainable development concept. This original scientific article analyses two income tax preferences – thermal modernisation tax relief and research and development tax relief – to verify whether the objectives for their introduction have been achieved. Special attention has been paid to issues experienced in practice in relation to the use of the aforementioned tax reliefs by taxpayers, leading to the conclusion that due to the number of doubts arising when trying to benefit from the tax reliefs and the often restrictive approach of tax authorities, these institutions do not provide optimal support for sustainable development goals. The applied research method was the dogmatic legal method, involving the determination of content, and the analysis, interpretation and exegesis of applicable law. Primary sources examined included foreign and national generally applicable legal acts, judgments, as well as individual and general tax rulings.
Keywords: sustainable development, income tax, thermal modernisation tax relief, research and development tax relief